2017
DOI: 10.7860/jcdr/2017/22600.9479
|View full text |Cite
|
Sign up to set email alerts
|

Study of Glycated Haemoglobin (HbA1c) In Non-Diabetic Subjects with Subclinical Hypothyroidism

Abstract: Our data suggest that the non-diabetic subjects with SH show misleadingly high levels of the HbA1c. Therefore, the effect of altered levels of the serum TSH on the HbA1c must be considered when interpreting the HbA1c for the diagnosis of diabetes in the SH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…This finding was consistent with the results of Khalid et al, who did not find any association between T2DM and hypothyroidism [ 18 ]. Our finding was in contrast to the findings of Ezeani et al [ 16 ], Cho et al [ 19 ], and Makadia et al [ 20 ], who found a strong association of HbA1c with thyroid dysfunction. We demonstrated no association between SCH and poor glycemic control in patients with T2DM.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding was consistent with the results of Khalid et al, who did not find any association between T2DM and hypothyroidism [ 18 ]. Our finding was in contrast to the findings of Ezeani et al [ 16 ], Cho et al [ 19 ], and Makadia et al [ 20 ], who found a strong association of HbA1c with thyroid dysfunction. We demonstrated no association between SCH and poor glycemic control in patients with T2DM.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we found a significant positive association between subclinical hypothyroidism and HbA1c ( Table 3 ). This is consistent with the findings of a previous study that reported the levels of HbA1c in non-diabetic participants with subclinical hypothyroidism to be higher than those in normal healthy controls [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another cross-sectional study reported that the levels of HbA1c in non-diabetic participants with subclinical hypothyroidism were significantly higher than those in normal healthy controls [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] A significant correlation between TSH and HbA1c serum levels has also been found. 18 Low RBC turnover, with a predominance of older cells are associated with a falsely elevated HbA1c. Proven examples include iron and vitamin B12 deficiencies and renal failure.…”
Section: Introductionmentioning
confidence: 99%